A Role for Notch Signalling in Breast Cancer and Endocrine Resistance - Ahmet Acar; Bruno M. Simões; Robert B. Clarke; Keith Brennan (Hindawi Limited, 2016)
Over the past decade, there has been growing interest in the Notch signalling pathway within the breast cancer field. This interest stemmed initially from the observation that Notch signalling is aberrantly activated in breast cancer and its effects on various cellular processes including proliferation, apoptosis, and cancer stem cell activity. However more recently, elevated Notch signalling has been correlated with therapy resistance in oestrogen receptor-positive breast cancer. As a result, inhibiting Notch signalling with therapeutic agents is being explored as a promising treatment option for breast cancer patients.